Digital culture: New literacies in remixed transmedia narrative texts in transgressive Portuguese Language teaching - Santos, Thiago; Lacerda, Naziozênio Antonio (The ESPecialist, 2024)
This research falls within the field of Applied Linguistics and aims to investigate the new literacies in remixed transmedia narrative texts in Portuguese Language teaching from a transgressive viewpoint in the context of digital culture. The research has a theoretical basis in Jenkins (2006), Lankshear and Knobel (2011), Rojo and Moura (2019) and Tavares and Cruz (2016). The methodology adopts a qualitative approach, characterized as descriptive, documentary and applied, to study a corpus consisting of three media: musical album, documentary film and social network posts from the transmedia universe "AmarElo", authored by singer-songwriter Emicida. The results of the analysis of the transmedia narrative show the following remixing operations: remix, sampling, video mashup and motion graphics. It is concluded that the new literacies in remixed transmedia narrative texts can be worked in the transgressive Portuguese Language teaching, contributing to students' participation in a new mindset in digital culture.